The official football match-fixing prevention discourse as a cognitive limitation (the cases of Iberian countries) - Moriconi, M. (Soccer and Society, 2018)
This paper shows the cognitive and educational limitations of the official institutional discourse to combat match-fixing in football. Recently, after reaching the political and sports’ institutional agendas, several reports have been published and official prevention campaigns have been launched to fight against the phenomenon. These documents can be understood as an official preventive narrative on the subject. The discursive analysis of the ‘nodal points’ in which this narrative is based displays a lack of holistic awareness of the problem. Many discursive variables that should be part of the diagnoses are avoided. Likewise, the narrative is presented with a universal character, yet the Iberian cases present evidences that contradict it. Based on interviews to key informants and media clipping, this paper shows that these preventive and educational messages produced by international institutions and sport organizations are not useful in Portugal or Spain because they don’t show the reality about this phenomenon.